Mitochondria and Cell Death - Hockenbery, David M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana Press, 2016)
This volume examines the role of mitochondria in different types of cell death, including apoptotic and necrotic cell deaths. Topics discussed include mitochondrial outer membrane permeabilization (MOMP) and the permeability transition pore; core processes such as calcium handling, fission and fusion, reactive oxygen species generation, and maintenance of mitochondrial DNA fidelity and protein folding homeostasis; and retrograde signaling between mitochondria and other cellular components, including the important role of mitochondria in antiviral immunity. The expertly authored chapters are drawn from multidisciplinary international perspectives, lending a nuanced and comprehensive approach to the material. Mitochondria and Cell Death, part of the Cell Death in Biology and Diseases series, is invaluable reading for graduate students, researchers, and clinicians in the fields of neuroscience, oncology, gastroenterology, and hepatology, as well as those interested in the study of mitochondria and cell biology.
Preface -- 1.Lethal and non-lethal functions of the permeability transition pore -- 2.Mitochondrial Calcium and Ischemia-Reperfusion Injury in Heart -- 3.Mislocalization of mitochondrial intermembrane space proteins -- 4.Bcl-2 protein interplay on the outer mitochondrial membrane -- 5.Remodeling of Mitochondria in Apoptosis -- 6.Physiologic and Pathologic Functions of Mitochondrial ROS -- 7.Mitochondrial Mutagenesis in Cancer -- 8.Mitochondrial UPR in cancer -- 9.Mitochondrial signaling -- 10.Mitochondria and antiviral immunity -- 11.Mitochondrial permeabilization from lethality to vitality -- Index.
Keywords: Life sciences; Cell cycle; Cell membranes; Apoptosis; Life Sciences; Apoptosis; Membrane Biology; Cell Cycle Analysis; Electronic books